Realization of the Nersesyan-Tsvelik model in (NO) (Cu(NO3)3) - Volkova, Olga; Morozov, I.; Shutov, V.; Lapsheva, E.; Sindzingre, P.; Cépas, O.; Yehia, M.; Kataev, V.; Klingeler, Rüdiger; Büchner, B.; Vasiliev, A. (Physical review. B, Condensed matter and materials physics, 2010)
The topology of the magnetic interactions of the copper spins in the nitrosonium nitratocuprate (NO)[Cu(NO3)3] suggests that it could be a realization of the Nersesyan-Tsvelik model [A. A. Nersesyan and A. M. Tsvelik, Phys. Rev. B 67, 024422 (2003)], whose ground state was argued to be either a resonating valence-bond state or a valence-bond crystal. The measurement of thermodynamic and magnetic resonance properties reveals a behavior inherent to low-dimensional spin S=12 systems and provides indeed no evidence for the formation of long-range magnetic order down to 1.8 K.
Im Titel erscheint in der chemischen Formel der Teil Cu(NO3)3 in eckigen Klammern und die Ziffer 3 ist jeweils tiefgestellt
Gesehen am 12.09.2023